Proceedings of the 4th Workshop on Embedded Networked Sensors 2007
DOI: 10.1145/1278972.1278979
|View full text |Cite
|
Sign up to set email alerts
|

Software-based on-line energy estimation for sensor nodes

Abstract: Energy is of primary importance in wireless sensor networks. By being able to estimate the energy consumption of the sensor nodes, applications and routing protocols are able to make informed decisions that increase the lifetime of the sensor network. However, it is in general not possible to measure the energy consumption on popular sensor node platforms. In this paper, we present and evaluate a softwarebased on-line energy estimation mechanism that estimates the energy consumption of a sensor node. We evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
174
0
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(182 citation statements)
references
References 14 publications
1
174
0
7
Order By: Relevance
“…Nevertheless, we have observed that Contiki's software-based online energy estimation [2] reports approximately 14 % increased transmit energy consumption when using our approach. This is caused by the fact that by default, the estimation mechanism only counts frames that are sent in software.…”
Section: F Power Consumptionmentioning
confidence: 80%
“…Nevertheless, we have observed that Contiki's software-based online energy estimation [2] reports approximately 14 % increased transmit energy consumption when using our approach. This is caused by the fact that by default, the estimation mechanism only counts frames that are sent in software.…”
Section: F Power Consumptionmentioning
confidence: 80%
“…It can be considered as an indicator of power consumption and describes the energy efficiency of the protocol. We measure radio-on time by using the software-based energy profiler [16] provided by Contiki.…”
Section: Metricsmentioning
confidence: 99%
“…Through the facilities provided by Contiki's energy consumption estimation module, (Energest [9]), we measured the time each node spent in different power consumption states (MCU active; RF listening / receiving, RF transmitting). Since we are simulating Texas Instruments MSP430F5438 experimenter board nodes, we converted these time values to estimated energy consumption based on typical datasheet power consumption levels at an operating voltage of 3.0V .…”
Section: Energy Consumptionmentioning
confidence: 99%